Productivity of tomato hybrids cultivated in aquaponia associated in a floating type system (Research, Society and Development, 2020)
A laboratory research aimed to evaluate the productivity of 5 tomato hybrids (Apolo, Serato, Vento, Candieiro and Pioneiro) in an aquaponic system associated with tilapia breeding. The experimental design was completely randomized, with 5 treatments (tomato varieties) and four replications. Each repetition comprises a cultivation block, an area of ​​one square meter with 6 plants. The water parameters of the system were monitored: dissolved oxygen, pH, electrical conductivity, minimum and maximum temperature. The harvest was carried out weekly between the period from 01/05/2018 to 01/24/2018, totaling four harvests. At the time of harvest, the weight and measurements of each fruit (transverse diameter and longitudinal length) were determined. The results were obtained through analysis of variance by the F test and the means compared by the Tukey test, at 5% probability. The Apolo hybrid was the one with the highest average total productivity (104.53 t ha-1), with productivity increases ranging from 19 to 61% in relation to the other hybrids. The productivity achieved can be considered high and equivalent to values ​​cultivated in conventional cultivation, in soil.